Huang Qi Tong Bi Decoction Attenuates Myocardial Ischemia-Reperfusion Injury via HMGB1/TLR/NF-κB Pathway - Kun Liu; Manman Li; Xiumei Ren; Qing-sheng You; Fei Wang; Shuo Wang; Chun-Hui Ma; Wei-Nan Li; Qing Ye (Mediators of Inflammation)
The aim of this study was to study the protective effect of Huang Qi Tong Bi Decoction (HQTBT) on the heart of rats. Ischemia-reperfusion injury was established by coronary artery ligation. Proinflammatory cytokines were decreased by XFZY in coronary artery ligated rats. ST segment was also restored with the treatment of HQTBT. Triphenyltetrazole chloride (TTC) staining and pathological analysis showed that HQTBT reduced myocardial injury. Besides, the expressions of HMGB1/TLR/NF-κB pathway in rats were significantly decreased by HQTBT. This study shows that HQTBT inhibited inflammatory reaction on myocardial injury in rats.